25=(-3+5r)-3(r-4)

Simple and best practice solution for 25=(-3+5r)-3(r-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25=(-3+5r)-3(r-4) equation:


25=(-3+5r)-3(r-4)

We simplify the equation to the form, which is simple to understand
25=(-3+5r)-3(r-4)

Remove unnecessary parentheses
25=-3+5r-3*(r-4)

Reorder the terms in parentheses
25=-3+5r+(-3r+12)

Remove unnecessary parentheses
+25=-3+5r-3r+12

We move all terms containing r to the left and all other terms to the right.
-5r+3r=-3+12-25

We simplify left and right side of the equation.
-2r=-16

We divide both sides of the equation by -2 to get r.
r=8

See similar equations:

| 5z+2[3(1-z)-2(1+z)]=12 | | 6x=x+14 | | 61=-3(5k-4)-2(k+1) | | 5B-30=50 | | 9x+3y=114 | | 175000.00+550.00=35000.00+1680.00x | | 3x-12+2x=-3+14 | | -18-6k=-3(1-3k) | | [x]-6=12 | | (5x+2)3= | | 1.5(x+8)=4.3+0.8x | | 10a-a= | | 18c-29c=151-30 | | 0.6x+1.5=-0.6(2x+5) | | 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 | | 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 |

Equations solver categories